2019
DOI: 10.3389/fvets.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

A Computed Tomographic and Pathological Study of Equine Cheek Teeth Infundibulae Extracted From Asymptomatic Horses. Part 2: MicroCT, Gross, and Histological Findings

Abstract: Background: Equine maxillary cheek teeth infundibulae are frequently affected by developmental and acquired disorders, but the imaging, gross, and histological features of normal and abnormal infundibulae remain incompletely understood. Objective: To perform MicroCT, gross examination, and histology on sectioned teeth and compare the imaging and anatomical findings. Study design: Ex vivo original study. Methods: Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The short length crowns are brachydont and are adapted for soft diet and the hypsodont ones for long crowns are suitable for harder and dry food. Although previous radiological studies have been performed on the teeth of camel and equines [ 19 – 22 ], the dental cusps configurations have been neglected by many researchers [ 23 , 24 ]. Surprisingly, we are not aware of any studies addressing the morphological characteristics of camel teeth, and therefore, the present work aimed to provide more anatomical knowledge about the teeth of one-humped camel, in addition to clarifying the arrangement pattern of its dental cusps.…”
Section: Introductionmentioning
confidence: 99%
“…The short length crowns are brachydont and are adapted for soft diet and the hypsodont ones for long crowns are suitable for harder and dry food. Although previous radiological studies have been performed on the teeth of camel and equines [ 19 – 22 ], the dental cusps configurations have been neglected by many researchers [ 23 , 24 ]. Surprisingly, we are not aware of any studies addressing the morphological characteristics of camel teeth, and therefore, the present work aimed to provide more anatomical knowledge about the teeth of one-humped camel, in addition to clarifying the arrangement pattern of its dental cusps.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported on the development and anatomic structure of the cheek tooth infundibula. [21][22][23][24][25] These reports have focused on the development, [26][27][28] and therapy, [29][30][31][32] of infundibular cemental hypoplasia and infundibular caries. The authors are unaware of previous reports examining the timing of infundibular senescence in cheek teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The use of micro‐CT (µ‐CT) has been recommended to characterize microstructural features of bone and soft tissues to obtain, in a non‐destructive manner, accurate 2D images in invertebrate and vertebrate samples (de Bournonville, Vangrunderbeeck, & Kerckhofs, 2019; de Crespigny et al., 2008; Descamps et al., 2014; Gignac & Kley, 2014; Heimel et al., 2019; Koç, Aslan, Kao, & Barber, 2019; Metscher, 2009; Pauwels, Van Loo, Cornillie, Brabant, & Van Hoorebeke, 2013; Rüegsegger, Koller, & Müller, 1996; Shearer, Bradley, Hidalgo, Sherratt, & Cartmell, 2016; Swain & Xue, 2009). In veterinary research, µ‐CT studies have mainly focused on the locomotor apparatus and associated diseases (Dedrick et al., 1993; Horbal, Smith, & Dixon, 2019; Lill, Gerlach, Eckhardt, Goldhahn, & Schneider, 2002; Salmon, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary research, µ-CT studies have mainly focused on the locomotor apparatus and associated diseases (Dedrick et al, 1993;Horbal, Smith, & Dixon, 2019;Lill, Gerlach, Eckhardt, Goldhahn, & Schneider, 2002;Salmon, 2020).…”
mentioning
confidence: 99%